2010
DOI: 10.1007/s13233-010-0409-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silica based fillers, surface treatment and curing method on mechanical properties of silica/unsaturated polyester composites

Abstract: This study examined the effects of silica based fillers, precipitated silica (PSi) and silica from fly ash (FASi), and a silane treatment on the mechanical and morphological properties of unsaturated polyester (UPE) resins cured by conventional thermal (CV) and microwave (MW) curing methods. The curing curves for unfilled UPE in both curing systems exhibited S-shaped character. The curing curves for PSi/UPE composites were different from those of the FASi/UPE composites due to differences in the number of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 21 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…18 Previous works had reported that the addition of inorganic fillers will normally increase the modulus of the polymer composites. 19,20 However, the results presented in Figure 10 indicates that only composites filled with silane-treated silica were found to show increasing trend in flexural modulus with the increase in filler content. The influence of surface contact between fillers and polymer matrix was reported to have minimal effect to the flexural modulus of polymer composites.…”
Section: Impact Propertiesmentioning
confidence: 96%
“…18 Previous works had reported that the addition of inorganic fillers will normally increase the modulus of the polymer composites. 19,20 However, the results presented in Figure 10 indicates that only composites filled with silane-treated silica were found to show increasing trend in flexural modulus with the increase in filler content. The influence of surface contact between fillers and polymer matrix was reported to have minimal effect to the flexural modulus of polymer composites.…”
Section: Impact Propertiesmentioning
confidence: 96%
“…This implies that the c-MWCNTs caused an increase in the collision factor of the reactive species around the vicinity in the cross-linking system. Therefore, this resulted in an auto-acceleration reaction of the epoxidized soybean oil/citric acid/c-MWCNTs bionanocomposite system (Wang et al, 2012a,b;Sriloy et al, 2010). Moreover, the incorporation of c-MWCNTs increases the activation energy of the reactive species and thereby hastens the rate of cross-linking reaction.…”
Section: Curing Study and Mechanical Propertiesmentioning
confidence: 99%